Optimization of Monetary Corporate Social Responsibility Value Added in Reducing Financial Distress in Indonesia - Tristiarini, Nila; Setiawanta, Yulita; Pratiwi, Ririh Dian (International Journal of Economics and Financial Issues, 2017)
This study tried to investigate about a form of solution model and new empirical evidence which is not only related to how the effect of the application of Corporate Social Responsibility (CSR) to improve financial performance but also the measurement of benefits and costs of CSR activities as corporate strategy that allows to reduce financial distress so as to improve the financial performance of the company. The study sample was the whole companies which are included in the SRI-KEHATI index in 2009 to 2015, a total sample of 175 companies. This study used analysis tools SEM with a 3.00 version WarpPLS program to test the hypothesis. Outcomes of this research is that company can determine the optimization of CSR in terms of benefits and costs so that it can be used as a strategy for policy making in implementing CSR activities that can have positive implications on the sustainability of the company. Keywords: Corporate Social Responsibility, Financial Distress Reduction, Financial Performance, Financial Risk Management JEL Classifications: G1, G3, M4